The Meaning Of Bali Aesthetic Code In The Animated Film Si Uma - Hasbullah Hasbullah; I Wayan Mudra; I Wayan Swandi (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2021)
This study aims to analyze the meaning of aesthetic code in the animated film "Si Uma." The animated film "Si Uma" needs to be investigated because the reanimated film shows Balinese culture's beauty and has a unique character shape. Visualization of Balinese culture in this animated film contains a meaningful message for the life of the universe hitch conveyed through the form of code. The problem is what is the meaning of the Balinese aesthetic code represented in the animated film "Si Uma." The method used in this research is qualitative with data collection techniques through observation, interviews, and documentation. The technique of determining the source of data in this study is the Snowball sampling technique. Data sources were collected through interviews with Ida Bagus Surya Manuba, I Nyoman Suci Rasika, and Gede Pasek Putra Adnyana Yasa. Data analysis was carried out through data reduction, presentation, and conclusion drawing based on Ferdinand de Saussure's semiotic theory and Roland Barthes' postmodern aesthetic code. The results of this study indicate that the aesthetic code in the animated film "Si Uma" in the form of a semantic code is associated with a black and white patterned fabric sign (poleng) which contains the meaning of life balance in the universe; the cultural code is associated with a headband (udeng) containing meaning to concentrate thoughts or views (concentration) in every activity in Bali. In conclusion, the meaning of the aesthetic code in the animated film "Si Uma" is seen from two perspectives such as : the semantic code in the form of Poleng Cloth is ideological containing the meaning of balance in life in the universe; cultural code in the form of a headband (udeng)is connotative which means to focus attention/thought, aesthetic, and cultural identity in worship and daily activities.